Hubungan Occupational Balance dengan Faktor Risiko Gangguan Kardiovaskular pada Mahasiswa - Hendri Kurniawan; Haryanti Haryanti (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: The university environment influences students' activity patterns, which impact occupational balance. Occupational balance is related to health and well-being. Blood pressure is an indicator of cardiovascular risk, influenced by a person's activity patterns. Objectives: This study aims to determine the relationship between occupational balance and blood pressure as a risk factor for cardiovascular disorders in students. Methods: The study used a quantitative observational method with a cross-sectional design. The study was conducted at the Occupational Therapy Department of the Health Polytechnic of the Ministry of Health, Surakarta. The study population was second and third-year students of the Applied Bachelor of Occupational Therapy Study Program, with a sample of 218 people (total sampling). The occupational balance (OB) variable was measured using the Occupational Balance Questionnaire (OBQ), while blood pressure was measured using a digital sphygmomanometer. Data were analyzed using the Pearson test and linear regression using SPSS version 25. Results: The majority of study subjects had good OB (89.4%), and normal blood pressure (61.9%). Good OB tended to have normal blood pressure (67.7-68.7%). OB was significantly negatively correlated (p<0.05) with both systolic (r=-0.463) and diastolic (r=-0.542) blood pressure. OB affected systolic blood pressure by 21.4% (Y=154.60-1.288X), while diastolic blood pressure was affected by 29.6% (Y=107.91-1.029X). Conclusion: Occupational balance was significantly negatively correlated with blood pressure in the moderate category in college students. OB affected both systolic and diastolic blood pressure in college students. Keywords: Students, Occupational Balance, Blood Pressure, Cardiovaskular.